The Effectiveness of Using the Song Hokey Pokey to Improve English Pronunciation Skills of Elementary School Students in Pedagogia - Ambarwati, Lina; Khaq, Muflikhul; Saputri, Mita; Putri, Raudya Setya Wismoko (Indonesian Research Journal on Education, 2025)
Pronunciation is an important aspect of English learning, especially at the elementary school level. However, many students experience difficulties in pronouncing vocabulary due to monotonous teaching methods and minimal phonological stimulation. This study aims to test the effectiveness of using the Hokey Pokey song in improving elementary school students' pronunciation skills. This study employed a quantitative approach with a quasi-experimental design of one-group pretest-posttest. The study sample consisted of 24 fourth-grade students who were given treatment in the form of learning using the Hokey Pokey song for four meetings. The research instrument was a pronunciation test before and after the treatment. Data were analyzed using a paired sample t-test. The results show an increase in the average pronunciation score from 63.75 in the pretest to 79.58 in the posttest, with a difference of 15.83 points. The t-test results show a significance value of 0.000 (p < 0.05), which indicates that the use of the Hokey Pokey song has a significant effect on improving students’ pronunciation skills. Song-based learning not only provides repetitive and rhythmic phonological practice but also creates a pleasant learning atmosphere, reduces psychological barriers, and increases students’ active participation. Thus, children’s songs like Hokey Pokey can be used as an alternative, effective pronunciation learning medium, adapting to students' learning styles, and promoting more comprehensive English language skills. These findings are relevant for application in thematic learning contexts and multilingual literacy-based curricula at the elementary level.